Organic Vs. Inorganic Mineral Supplements in Poultry: Availability and Physiological Effects: Subject Review - Noaman, H. A.; Mohammed, Diyar Jaafar (American Journal of Biology and Natural Sciences, 2025)
Trace minerals are indispensable for poultry, which are involved in growth, immune system, bone development and antioxidative ability. This review provides a comparative overview of organic and inorganic mineral supplementation with respect to its bioavailability, physiological effects, and sustainability to the environment. The organic minerals, such as the amino acid chelates and proteinates, have been observed to have better absorption, better feed use and reduced mineral excretions as compared with the inorganic forms, such as sulfates and oxides. The paper also addresses regulatory standards, tissue residue implications and current research gaps, such as the necessity for standard definitions, new delivery systems (e.g. nano-minerals), and the requirement for long-term field trials. Attention is focused on the contribution of minerals (selenium, zinc, copper, manganese) to improve the performance of poultry and achieve environmental and food safety goals. The reconciliation of these international and regional findings (particularly those in recent studies conducted in the Kurdistan region) delineates the significance of mineral protection choice in sustainable poultry husbandry at large.